FGF21 improves cognition by restored synaptic plasticity, dendritic spine density, brain mitochondrial function and cell apoptosis in obese-insulin resistant male rats - Piangkwan Sa-nguanmoo (2018)
© 2016 Elsevier Inc. Fibroblast growth factor 21 (FGF21) is an endocrine hormone which exerts beneficial effects on metabolic regulation in obese and diabetic models. However, the effect of FGF21 on cognition in obese-insulin resistant rats has not been investigated. We hypothesized that FGF21 prevented cognitive decline in obese-insulin resistant rats by improving hippocampal synaptic plasticity, dendritic spine density, brain mitochondrial function and brain FGF21 signaling as well as decreasing brain cell apoptosis. Eighteen male Wistar rats were divided into two groups, and received either a normal diet (ND) (n = 6) or a high fat diet (HFD) (n = 12) for 12 weeks. At week 13, the HFD-fed rats were subdivided into two subgroups (n = 6/subgroup) to receive either vehicle or recombinant human FGF21 (0.1 mg/kg/day) for four weeks. ND-fed rats were given vehicle for four weeks. At the end of the treatment, cognitive function, metabolic parameters, pro-inflammatory markers, brain mitochondrial function, cell apoptosis, hippocampal synaptic plasticity, dendritic spine density and brain FGF21 signaling were determined. The results showed that vehicle-treated HFD-fed rats developed obese-insulin resistance and cognitive decline with impaired hippocampal synaptic plasticity, decreased dendritic spine density, brain mitochondrial dysfunction and increased brain cell apoptosis. Impaired brain FGF 21 signaling was found in these obese-insulin resistant rats. FGF21-treated obese-insulin resistant rats had improved peripheral insulin sensitivity, increased hippocampal synaptic plasticity, increased dendritic spine density, restored brain mitochondrial function, attenuated brain cells apoptosis and increased brain FGF21 signaling, leading to a prevention of cognitive decline. These findings suggest that FGF21 treatment exerts neuroprotection in obese-insulin resistant rats.